2014
DOI: 10.1037/cou0000027
|View full text |Cite
|
Sign up to set email alerts
|

AAPI college students’ willingness to seek counseling: The role of culture, stigma, and attitudes.

Abstract: This study tested 4 theoretically and empirically derived structural equation models of Asian, Asian American, and Pacific Islanders' willingness to seek counseling with a sample of 278 college students. The models represented competing hypotheses regarding the manner in which Asian cultural values, European American cultural values, public stigma, stigma by close others, self-stigma, and attitudes toward seeking professional help related to willingness to seek counseling. We found that Asian and European Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 55 publications
(179 reference statements)
7
43
1
1
Order By: Relevance
“…As for nationality, many studies confirmed a relationship between cultural background and help‐seeking when considering differences between Asian and other ethnic groups. For example, Brownson et al (), Cheng et al (), Choi and Miller (), and Kam et al () found that Asians had less favourable attitudes towards help‐seeking, less help‐seeking intentions and were less likely to seek help compared to other ethnic groups. Fourteen studies did not find a relationship.…”
Section: Resultsmentioning
confidence: 99%
“…As for nationality, many studies confirmed a relationship between cultural background and help‐seeking when considering differences between Asian and other ethnic groups. For example, Brownson et al (), Cheng et al (), Choi and Miller (), and Kam et al () found that Asians had less favourable attitudes towards help‐seeking, less help‐seeking intentions and were less likely to seek help compared to other ethnic groups. Fourteen studies did not find a relationship.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies used quantitative designs – either experimental designs ( n = 2; Y. J. Wong, Wang, et al, 2014; Zane & Ku, 2014) or correlational: cross-sectional designs, using analytical methods such as regression, path analysis, or analysis of variance ( n = 7; e.g., N.-Y. Choi & Miller, 2014) – while only one study used a qualitative design (interviews; L.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, although both perceived and personal stigma have been found to be relevant for Asian populations, perceived stigma has been shown to be higher in this population (Eisenberg et al, ), a finding which has been explained by literature indicating that Asian populations are more likely than their peers to avoid deviating from social norms (Yang et al, ). Furthermore, although not always differentiating between types, stigma, particularly perceived stigma, has been linked to negative attitudes toward professional psychological help seeking in Asian American populations (Choi & Miller, ; Miville & Constantine, ; Shea & Yeh, ).…”
Section: Stigma and Attitudes Toward Professional Psychological Help‐mentioning
confidence: 99%